Cluster observations of reflected EMIC‐triggered emission. Issue 9 (14th May 2016) - Grison, B.; Darrouzet, F.; Santolík, O.; Cornilleau‐Wehrlin, N.; Masson, A.
Abstract: On 19 March 2001, the Cluster fleet recorded an electromagnetic rising tone on the nightside of the plasmasphere. The emission was found to propagate toward the Earth and toward the magnetic equator at a group velocity of about 200 km/s. The Poynting vector is mainly oblique to the background magnetic field and directed toward the Earth. The propagation angle θ k, B 0 becomes more oblique with increasing magnetic latitude. Inside each rising tone θ k, B 0 is more field aligned for higher frequencies. Comparing our results to previous ray tracing analysis we conclude that this emission is a triggered electromagnetic ion cyclotron (EMIC) wave generated at the nightside plasmapause. We detect the wave just after its reflection in the plasmasphere. The reflection makes the tone slope shallower. This process can contribute to the formation of pearl pulsations. Key Points: Multispacecraft observations of a reflected EMIC‐triggered emission The reflection makes the rising tone slope shallower High abundance of O + ions is required to match the group velocity observations